TINJAUAN YURIDIS TERHADAP PERJANJIAN KREDIT PEMILIKAN RUMAH PADA PT. BANK RAKYAT INDONESIA (Persero) Tbk. DAN AKAD MURABAHAH PADA PT. BANK RAKYAT INDONESIA SYARIAH (Persero) Tbk. CABANG PURWOKERTO - Rakhma Nurrozalina (Jurnal Idea Hukum, 2015)
The important role which should be played by the national banking world for the present and forthcoming is positioning itself as one of the main pillars for national development oriented to the improvement of people's welfare. The economic development of a country, of course, indispensable presence settings regarding the management of economic resources available to run with directional and integrated. Research methods in this thesis using normative juridical approach. Based on the results of research and discussion on the subject matter presented in this thesis research, the results of this study is to analyze the comparative clause, the legal basis and purpose of the loan agreement with Bank BRI Bank BRIS murabaha contract, it can be found similarities and differences.While the banking system on the external control (conventional and sharia) conducted by BI, OJK, and specifically Islamic banks are supervision of DPS. There are 2 monitoring system conducted by BI is based compliance monitoring, risk-based supervision. Conditions of supervision of Bank Indonesia since the enactment of authority OJK dated December 31, 2013 has been restricted to macroprudential supervision as microprudential supervision was transferred to the OJK, but between BI and the OJK remains mutual correspondence. Supervision of DPS to Islamic banks is very important in maintaining and mengawasai that Islamic banking in running its operations remain in accordance with Islamic principles.Keywords : National banking, BRI syari’ah, Akad Murabbah